2016
DOI: 10.1038/ncomms13345
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-coated meshes for electroactive flow control devices utilizing two antagonistic functions of repellency and permeability

Abstract: The wettability of graphene on various substrates has been intensively investigated for practical applications including surgical and medical tools, textiles, water harvesting, self-cleaning, oil spill removal and microfluidic devices. However, most previous studies have been limited to investigating the intrinsic and passive wettability of graphene and graphene hybrid composites. Here, we report the electrowetting of graphene-coated metal meshes for use as electroactive flow control devices, utilizing two ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Ni or Cu mesh can be cut into any shape and size and applied as a catalytic substrate for CVD to achieve a GM with the desired shape . By etching the metallic skeleton, hollow tubes of graphene can be obtained and it can form a macroscale mesh‐type architecture woven with each other . Most importantly, the wavy pattern of the hollow tubular mesh structures renders them much more stretchable than other types of graphene architecture such as graphene paper.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Ni or Cu mesh can be cut into any shape and size and applied as a catalytic substrate for CVD to achieve a GM with the desired shape . By etching the metallic skeleton, hollow tubes of graphene can be obtained and it can form a macroscale mesh‐type architecture woven with each other . Most importantly, the wavy pattern of the hollow tubular mesh structures renders them much more stretchable than other types of graphene architecture such as graphene paper.…”
Section: Introductionmentioning
confidence: 89%
“…To obtain a free‐standing GM, the Ni was removed by soaking the samples in hot (80 °C) HCl solution (3 m ) for 24 h. By dissolving the Ni, the hollow graphene meshes floated to the top of the solution. The samples were washed with DI water and dried by freeze‐drying …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabassian et al reported electric-field-induced wetting of nickel meshes coated by graphene for use as flow control devices (Figure 9). [137] The droplet shapes and water penetration through the meshes can be controlled by an electric field. Based on electric-fieldinduced wetting, the CA of the conductive liquid (e.g., water) Figure 9.…”
Section: Electric-field-induced Selective Permeation For Separationmentioning
confidence: 99%
“…Reproduced with permission. [137] Copyright 2016, Nature Publishing Group. can be effectively reduced, while it has almost no effect on a nonconductive oil droplet in air, and the oil CA even increases in water.…”
Section: Electric-field-induced Selective Permeation For Separationmentioning
confidence: 99%